MORAL VALUE FROM THE CHARACTER OF ALAN TURING IN “THE IMITATION GAME” MOVIE - Budiarto Budiarto; Imaniar Imaniar; Suhendar Suhendar (STIBA IEC JAKARTA, 2021)
The objectives of this research are to describe to discover facts about Alan Turing and the impacts of the characters on his life in order to obtain the moral value of the movie. By using qualitative method, the author describes hidden facts about Alan Turing, especially when he was given a secret mission by the British Empire during World War II to decode from Germany’s Enigma message’s machine. In this movies, his personal life and sexual deviation influence his career. In order to keep his mission going, Turing, the professor pretends to be a normal person by trying love his partner, Ms Clark. He doesn’t get any respects and losses his dignity due to his own deviant behaviors. He is sentenced and has to receive hormone therapy to make him normal and continue his mission. His struggles continue although the government ignores his invention and dedication to his country.